2005
DOI: 10.4315/0362-028x-68.5.942
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Resistance of Heat-, Cold-, and Starvation-Injured Salmonella in Irradiated Comminuted Turkey

Abstract: To investigate the effects of sublethal stress on Salmonella thermal inactivation kinetics, an eight-strain Salmonella cocktail was subjected to heat shock (30 min at 54 degrees C), cold shock (2 h at 4 degrees C), and starvation stress (10 days in phosphate buffer at 4 degrees C), harvested by centrifugation, and inoculated into irradiated comminuted turkey. Immediately after stressing, the Salmonella cocktails contained 89.1% heat-injured, 44.7% cold-injured, and 67.7% starvation-injured cells, as determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 39 publications
1
22
0
Order By: Relevance
“…This culture was centrifuged three times for 25 min at 2,250 x g, and the pellet was washed with phosphate buffer (0.05 mM, pH 7). The cell population was adjusted to a level of 109 CFU/ml and refrigerated (4°C) for no more than 7 days before inoculation of almond kernel flour (35,42).…”
Section: A Ter Ia Ls a N D M E Th O D Smentioning
confidence: 99%
“…This culture was centrifuged three times for 25 min at 2,250 x g, and the pellet was washed with phosphate buffer (0.05 mM, pH 7). The cell population was adjusted to a level of 109 CFU/ml and refrigerated (4°C) for no more than 7 days before inoculation of almond kernel flour (35,42).…”
Section: A Ter Ia Ls a N D M E Th O D Smentioning
confidence: 99%
“…A 6.5-log unit reduction of Salmonella in cooked beef and roast beef and a 7.0-log unit reduction in certain fully and partially cooked poultry products were set as performance standards for lethality, stabilization, and product handling (Weche et al, 2005). Raw meat and poultry are usually considered ideal growth media for bacteria; however, all microbial contaminants are subjected to physical, chemical, and nutritional stresses during processing (Yousef and Courtney, 2003).…”
Section: Introduction S Ince Its First Recognition As a Foodbornementioning
confidence: 99%
“…With the production of heat-shock proteins, cells are able to adapt and, subsequently, better survive lethal temperatures (5,7). For example, Stephens et al (15) demonstrated that slow heating (<5°C/min) increased the thermotolerance of Listeria monocytogenes, and Wesche et al (22) reported enhanced Salmonella survival at 60°C in ground turkey previously heat shocked at 43°C for 5, 30, and 60 min. Wiegand et al (23) reported that inactivation parameters based on isothermal laboratory data generally overpredicted end-point lethality outcomes for Escherichia coli 0157:H7 in whole-muscle beef roasts slow-cooked in a pilot-scale oven.…”
mentioning
confidence: 97%